Navigating the Digital Transformation: Insights from Digital Library Strategic Development - Sholeh, Makherus; Fadhli, Muhammad (Islamic Educational Management Programme, 2023)
This research aims to explore the development strategies of digital libraries in Indonesian Islamic Higher Education Institutions (IHEIs). Using a qualitative method with descriptive surveys, the study gathers qualitative data from primary books, research journals, and conducts extensive literature reviews on digital library development and management strategies. Interviews with lecturers in IHEIs further enhance the research data. The findings highlight important aspects such as robust technological infrastructure, compatibility with existing systems, interoperability, and adequate storage. The research emphasizes the need for digital library management policies to address intellectual property rights, copyright compliance, open access principles, user adoption strategies, and long-term preservation and accessibility of digital content. The research provides valuable insights and recommendations for administrators, librarians, and IT personnel, contributing to the knowledge of digital library management in Islamic educational institutions and guiding strategic decision-making and resource allocation for their development and sustainability.